Obtenção e caracterização de extratos de folhas de yacon por líquido pressurizado sob diferentes condições de solvente e de temperatura - Souza, Larissa Lóren de (Universidade Federal de São Carlos, 2025)
The use of plants for medicinal purposes has been recorded throughout history. With scientific advances, it has been possible to identify some beneficial effects of plants related to the bioactive compounds present in them. Phenolic compounds stand out as bioactive compounds with antioxidant and anti-inflammatory capacity and potential for preventing cardiovascular diseases, cancer, neurodegenerative diseases, diabetes, osteoporosis and slowing down ageing. Still little known, yacon (Smallanthus sonchifolius) has demonstrated the presence of various classes of phenolics in its leaves, which makes it a promising natural resource that can be associated with emerging extraction technologies to obtain extracts rich in phenolic compounds with potential antioxidant action. Pressurized Liquid Extraction (PLE) and Subcritical Water Extraction (SWE), which in the literature have been shown to be efficient in recovering phenolic compounds, were used to obtain extracts from dried yacon leaves. The solvents used were ethanol 25% (v/v), ethanol 50% (v/v), ethanol 75% (v/v), ethanol 100% and pure water, at temperatures of 60, 90 and 120 °C, with extra points for water at 110, 130 and 150 °C. Subsequently, the extracts were characterized in terms of overall yield, total phenolics using the Folin Ciocalteu method, identification and quantification of phenolic compounds by ultraperformance liquid chromatography with photodiode array detector (UPLC-PDA), antioxidant capacity using the oxygen radical absorbance capacity (ORAC) and ferric reduction capacity (FRAP) methods, protein content using the Bradford method, in vitro anti-inflammatory activity, antimicrobial activity, minimum inhibitory concentration assay and analysis of antiquorum sensing activity. In addition, a comparison was made between emerging and conventional extraction methods using the Soxhlet technique. The results showed that increasing the temperature, combined with alcohol fractions of up to 50%, provided higher yields, as well as greater recovery of phenolic compounds and antioxidant capacity. In the chromatographic analysis, the main phenolic compounds identified were caffeic acid, glucaric acid, quercetin-O-hexoside and kaempferol derivatives. Five extracts showed antiinflammatory activity. The antimicrobial activity was evaluated against Lactococcus lactis ATCC 19435 by determining the minimum inhibitory concentrations. In addition, antiquorum sensing activity was assessed using Chromobacterium violaceum, enabling the direct observation of the inhibitory effect on violacein synthesis, which is regulated by this cell-tocell communication mechanism. The results highlight the promising potential of producing yacon leaf extracts through PLE, promoting a more sustainable process and yielding bioactive compounds with potential applications in the food, pharmaceutical, and cosmetic industries.
Obtaining and characterizing yacon leaf extracts by pressurized liquid under different solvent and temperature conditions
Keywords: Smallanthus sonchifolius; Extração; Compostos fenólicos; Atividade antioxidante.; Extraction; Phenolic compounds; Antioxidant activity; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::MICROBIOLOGIA DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS